Finite element analysis of progressive collapse resistance of a prefabricated RC frame structure with stud connection considering chloride corrosion - Zhiyuan Gao; Jiaolei Zhang (PLoS ONE, 2025)
To evaluate and ensure the safety of a prefabricated connection scheme for future engineering applications, this study investigates the life-cycle progressive collapse resistance of prefabricated reinforced concrete frame structures (PRCS) with steel tube stud connections. A simplified prefabricated column model was developed in SAP2000 using multi-segment linear plastic connection elements, and a six-story PRCS was established for analysis. Progressive collapse behavior of the PRCS and a comparable cast-in-place concrete frame structure (CPCS) was evaluated through the column removal method under four scenarios: corner column, long-side middle column, short-side middle column, and interior column removal. Time-history responses of internal forces and displacements were obtained. In addition, the effect of chloride-induced corrosion on the collapse performance of the structure was analyzed through pushdown analyses. The results indicate that the proposed connection model accurately reproduces the behavior of prefabricated column joints. Among the four scenarios, interior column removal had the most severe effect on PRCS, with displacement increasing by 72.2% compared to CPCS. Pushdown analysis revealed that PRCS exhibited 25.4% lower beam mechanism capacity when the corner column was removed, and 33.1% lower catenary mechanism capacity when the interior column was removed. Furthermore, long-term corrosion significantly reduced the progressive collapse capacity, underscoring the necessity of considering durability effects in design.